2023
DOI: 10.36834/cmej.75364
|View full text |Cite
|
Sign up to set email alerts
|

Intimidation or harassment among family medicine residents in Saskatchewan: a cross-sectional survey

Abstract: Introduction: Up to 98% of practicing family physicians, and over 75% of resident physicians in Canada experience abusive incidents. Despite the negative consequences of abusive incidents, few residents report these events to their supervisors or institution. We sought to estimate the prevalence of abusive incidents experienced or witnessed by Saskatchewan family medicine residents (FMRs) and identify their responses to these events. Methods: Anonymous survey invitations were emailed to all 110 Saskatchewan FM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…In their article, Intimidation or harassment among family medicine residents in Saskatchewan: a cross-sectional survey, 8 Coleman and team reported on the prevalence and response of abusive incidents experienced or witnessed by Saskatchewan family medicine residents. They observed that while most residents either experienced or witnessed abusive incidents, few reported those incidents.…”
Section: Brief Reportsmentioning
confidence: 99%
“…In their article, Intimidation or harassment among family medicine residents in Saskatchewan: a cross-sectional survey, 8 Coleman and team reported on the prevalence and response of abusive incidents experienced or witnessed by Saskatchewan family medicine residents. They observed that while most residents either experienced or witnessed abusive incidents, few reported those incidents.…”
Section: Brief Reportsmentioning
confidence: 99%